TEACHING METHODS IN THE LEARNING PROCESS (Ustozlar uchun, 2026)
At the core of any school is how we teach. It's not just about books and blackboards. In this paper, we examine how teaching methods have changed over the years. Analyzing old and new styles, we see a shift toward active learning. Clearly, the use of digital tools is making a significant difference in the classroom. In Uzbekistan, teachers are trying to change their approach to help students more effectively. This study examines why group work and project-based learning are beneficial. It also examines how teachers are using new technologies to reach every child. The conclusion shows that better teaching methods lead to better results. It's important to find a balance between the teacher's role and the student's own voice. This is how we develop as a society. It starts at the desk and extends to the entire world.